Changing patterns of adult asthma incidence: results from the National Health Insurance Service–National Sample Cohort (NHIS-NSC) database in Korea. Issue 1 (December 2018) - Shin, Ji-Yeon; Sohn, Kyoung-Hee; Shin, Ji; Park, Mira; Lim, Jiseun; Lee, Jin; Yang, Min-Suk
Abstract This study was conducted to assess the changes in the annual incidence of adult asthma in Korea where the prevalence of asthma had increased steadily in recent decades. A population-based cohort study was conducted using the National Health Insurance Service–National Sample Cohort (NHIS-NSC), which consisted of 746, 816 adults aged >20 years between 2004 and 2012. Asthma was defined by two or more physician claims on the basis of a primary diagnostic code for asthma and administration of asthma medications within 1 year. The incidence rates and annual percent change were calculated, and the influence of age and sex on the incidence rates was studied. The annual asthma incidence increased from 3.63 in 2004 to 6.07 per 1, 000 person-years in 2008. Since 2008, the asthma incidence did not change significantly. The asthma incidence was higher in women than in men throughout the study periods (p < 0.001) and higher in older than younger age groups (p < 0.001). The asthma incidence did not change in all ages since 2008, except for the 20 s who showed a steady increase. The incidence of asthma in adults reached plateau in Korea, which is consistent with the results from studies in other countries.